Recent Developments of Biopolymer-Based Composite Membranes as Sustainable Separators for Lithium-Ion Batteries - Tian Puspita Sari; Fitri Khoerunnisa; Asep Kadarohman (ALCHEMY Jurnal Penelitian Kimia, 2026)
The increasing adoption of electric vehicles and large-scale energy storage systems has intensified demand for high-performance and sustainable lithium-ion battery separators. This review summarizes recent progress in biopolymer-based separators as environmentally friendly alternatives to conventional polypropylene/polyethylene membranes. Fourteen research articles published between 2020 and 2026 are analyzed, focusing on biopolymers such as bacterial cellulose, chitosan, lignin, alginate, silk fibroin, and poly(L-lactic acid). The discussion covers material classification, membrane fabrication techniques, and modification strategies, including composite formation and crosslinking. Overall, the reviewed studies indicate that biopolymer-based separators generally exhibit improved electrolyte wettability, enhanced ionic conductivity, and adequate thermal stability, leading to competitive electrochemical performance and good cycling stability. In addition to performance benefits, the use of biomass-derived materials and water-based fabrication processes offers sustainability and potential biodegradability advantages. This review highlights current research trends and outlines key challenges related to testing standardization and manufacturing scalability for future lithium-ion battery applications.